PENGARUH FAKTOR MOTIVASI TERHADAP MINAT BERWIRAUSAHA MAHASISWA FARMASI - Honifa, Honifa; Kusumawati, Kurnia (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2024)
Interest in entrepreneurship is the concentration of attention on entrepreneurship due to a liking and a desire to learn, understand, and further prove oneself in entrepreneurship. Entrepreneurial interest arises from knowledge and information about entrepreneurship, which is then followed by direct participation in seeking experiences and ultimately a desire to pay attention to the experiences gained. It also involves a sense of joy and a desire to engage in risk-taking activities, to run one's own business or venture by utilizing existing business opportunities, and creating new businesses with innovative approaches. One of the factors influencing the emergence of Entrepreneurial Interest is Entrepreneurial Motivation. This study aims to determine the influence of Ambition for Freedom, Self-realization, and Pushing Factors on the entrepreneurial interest of pharmacy students. The method used in this research is quantitative descriptive method with the independent variables being Ambition for Freedom (X1), Self-realization (X2), Pushing Factors (X3), and the dependent variable being entrepreneurial interest. The sample in this study consisted of 116 pharmacy students from Universitas Pakuan and Poltekes Genesis Medicare who had taken entrepreneurship courses, selected using Nonprobability Sampling techniques. Data analysis was conducted using descriptive analysis and multiple linear regression analysis. The results of this research show that there is an influence of Ambition for Freedom, Self-realization, and Pushing Factors on the entrepreneurial interest of pharmacy students.